Integrating Gene Regulatory Network Dynamics with Heterogeneous Stem Cell Regeneration (CSIAM Transactions on Life Sciences, 2025)
Stem cell regeneration is crucial for development and maintaining tissuehomeostasis in self-renewing tissues. The dynamics of gene regulatory networks(GRNs) play a vital role in regulating stem cell renewal and differentiation. However,integrating the quantitative dynamics of GRNs at the single-cell level with population-level stem cell regeneration poses significant challenges. This study presents a computational framework that links GRN dynamics to stem cell regeneration through an inheritance function. This function captures epigenetic state transitions during cell division in heterogeneous stem cell populations. Our model derives this function usinga hybrid approach that integrates cross-cell-cycle GRN dynamics, effectively connecting cellular-level GRN structures with population-level regeneration processes. By incorporating GRN structure directly into stem cell regeneration dynamics, this framework simulates cross-cell-cycle gene regulation using individual-cell-based models.The scheme is adaptable to various GRNs, providing insights into the relationship between gene regulatory dynamics and stem cell regeneration. Additionally, we proposea future perspective that integrates single-cell ribonucleic acid sequencing data, GRNanalysis, and cell regeneration dynamics using AI-driven tools to enhance the precision of regenerative studies.